ANALISIS PERUBAHAN PENUTUPAN LAHAN DAN FAKTOR PENDORONG PENGGUNAAN LAHAN KAWASAN HUTAN DESA LAIYA, MAROS - Sabar, Adrayanti; Ansar; Alam, Syamsu; Halis, Ardian; Afdal, Muhammad (Forestry Study Program University Of Mataram, 2024)
Land cover change is strongly influenced by land use. Increasing population growth results in the need for food and other needs. The causes of land use change are influenced by human activities or activities that directly affect land use. Physical, social and economic factors are factors that trigger land use change in Laiya Village, Cenrana District. The purpose of this study was to describe land cover change in Laiya Village, Cenrana Subdistrict for the period 2011, 2015 and 2019 and to determine the driving factors that influence land use change around the forest area of Laiya Village. This research uses GIS analysis to analyze and see land cover changes that occur and qualitative descriptive methods to determine land use changes. The period 2011-2015 mixed dryland agriculture decreased in area by 2,893.19 ha while shrubs increased in area by 2,744.51 ha. The period 2015-2019 mixed dryland agriculture experienced an increase in land area of 3,030.64 ha and shrubs experienced a decrease in land area of 2,744.51 ha. Factors that influence land use change are physical, social and economic factors. Socio-economic factors are the main driving factor of land use change, the need for land for settlements is increasing due to the high population density that occurs around the forest area of Laiya Village, Cenrana District, Maros Regency which causes people to utilize land as an economic source.